2022
DOI: 10.1097/rlu.0000000000004248
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous Cholecystitis Masquerading as Gallbladder Carcinoma on 68Ga-FAPI-04 PET

Abstract: 68Ga-FAPI-04 has great potential for the detection and staging evaluation of a variety of tumors. We report a case of suspected gallbladder carcinoma that was enrolled in a prospective study of 68Ga-FAPI-04 imaging at our institution. This case was later histopathologically confirmed as xanthogranulomatous cholecystitis. This demonstrates that xanthogranulomatous cholecystitis might be disguised as gallbladder carcinoma in 68Ga-FAPI-04 imaging. Thus, we suggest that nuclear clinicians evaluating 68Ga-FAPI-04 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…Here we are presenting 3 patients with GB uptake. FAPI uptakes in GB and hepatobiliary system have been reported in literature review 9–12 . Subsequent hepatobiliary ultrasound and liver function enzymes demonstrated that none of these patients had liver metastasis or other liver or GB diseases.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Here we are presenting 3 patients with GB uptake. FAPI uptakes in GB and hepatobiliary system have been reported in literature review 9–12 . Subsequent hepatobiliary ultrasound and liver function enzymes demonstrated that none of these patients had liver metastasis or other liver or GB diseases.…”
mentioning
confidence: 85%
“…FAPI uptakes in GB and hepatobiliary system have been reported in literature review. [9][10][11][12] Subsequent hepatobiliary ultrasound and liver function enzymes demonstrated that none of these patients had liver metastasis or other liver or GB diseases. Case 1 presented a 60-year-old man with stage IV (according to TNM staging) lung adenocarcinoma (GB SUV max of 5.9 and SUV mean of 3.47, on the delayed phase with SUV max of 2.1 and SUV mean of 1.2 on the early ones).…”
Section: Figurementioning
confidence: 99%
“…We speculate that the high accumulation of 68 Ga-FAPI-04 in AVM stems from the uptake by the activated fibroblasts. Meanwhile, an increasing number of case studies have reported 68 Ga-FAPI-04 uptake in various nonmalignant etiologies, including myocardial infarction, 6 IgG4-related disease, 7,8 atherosclerotic plaque, 9 xanthogranulomatous cholecystitis, 10 tuberculosis, 11 osteoarthritis, 12 ankylosing spondylitis, 13 and brucellosis 14 . This case indicates that AVM should be considered as one of the differential diagnoses for abnormal 68 Ga-FAPI-04 uptake in the liver.…”
mentioning
confidence: 89%
“…[3][4][5] Gallbladder mass exhibits intense 68 Ga-FAPI uptake, including xanthogranulomatous cholecystitis and gallbladder adenocarcinoma. 6,7 The incidence of primary gallbladder small cell neuroendocrine carcinoma is 0.2% of all neuroendocrine tumors. 2,8,9 This rare neuroendocrine carcinoma has a high malignancy potential and low survival rate.…”
mentioning
confidence: 99%
“…68 Ga-FAPI is a promising fibroblast-activating protein imaging agent 3–5 . Gallbladder mass exhibits intense 68 Ga-FAPI uptake, including xanthogranulomatous cholecystitis and gallbladder adenocarcinoma 6,7 . The incidence of primary gallbladder small cell neuroendocrine carcinoma is 0.2% of all neuroendocrine tumors 2,8,9 .…”
mentioning
confidence: 99%